Applications to nuclear properties of the microscopic–macroscopic model based on the semiclassical Wigner–Kirkwood method. (29th October 2015) - Viñas, X; Bhagwat, A; Centelles, M; Schuck, P; Wyss, R
Abstract: Some time ago we proposed a new microscopic–macroscopic model where the semiclassical Wigner–Kirkwood expansion of the energy up to fourth-order in ℏ is used to compute the shell corrections in a deformed Woods–Saxon potential instead of the usual Strutinsky averaging scheme. For a set of 558 even–even nuclei computed with this new model, we found a rms deviation of 610 keV from the experimental masses, similar to the value obtained using the well-known finite range droplet model and the Lublin–Strasbourg drop model for the same set of nuclei. In this paper we analyze the α radioactivity in nuclei with mass number, finding good agreement with the available experimental results. We have also estimated spontaneous fission half-lives for superheavy nuclei in the region between Z = 102 and Z = 110. We find that our model predicts reasonably well the experimental half-lives in the considered nuclei, in spite of the fact that the fission barriers turn out to be somewhat too high.